2020
DOI: 10.1101/2020.01.21.913582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cultural variation impacts paternal and maternal genetic lineages of the Hmong-Mien and Sino-Tibetan groups from Thailand

Abstract: The Hmong-Mien (HM) and Sino-Tibetan (ST) speaking groups are known as hill tribes in Thailand; they were the subject of the first studies to show an impact of patrilocality vs. matrilocality on patterns of mitochondrial (mt) DNA vs. male-specific portion of the Y chromosome (MSY) variation. However, HM and ST groups have not been studied in as much detail; here we report and analyze 234 partial MSY sequences (∼2.3 mB) and 416 complete mtDNA sequences from 14 populations that, when combined with our previous p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…FADS-rs174570 had the top selection signal (PBS=0.2533). Previous genetic studies have reported that FADS levels were associated with Lipid Metabolism Disorder and Hypobetalipoproteinemia (31) (32). Ancient Southern Chinese people experienced a long history of infectious diseases.…”
Section: Natural Selection Signatures and Biological Adaptationmentioning
confidence: 98%
See 2 more Smart Citations
“…FADS-rs174570 had the top selection signal (PBS=0.2533). Previous genetic studies have reported that FADS levels were associated with Lipid Metabolism Disorder and Hypobetalipoproteinemia (31) (32). Ancient Southern Chinese people experienced a long history of infectious diseases.…”
Section: Natural Selection Signatures and Biological Adaptationmentioning
confidence: 98%
“…One of the typical representatives was Hainan Li, which had a relatively isolated genetic background and complex evolutionary history (13,37). Therefore, the genetic origin and phylogenetic relationship within TK-speaking populations remained to be further characterized (32,(40)(41)(42). We collected and genotyped 24 Bouyei individuals from Guizhou Bannong and merged newly-generated data with previously published data to produce three datasets: low-density merged HO dataset (26,27); middle-density merged 1240K dataset, and high-density merged WGS dataset (43)(44)(45)(46)(47)(48)(49) to provide new insights into the demographic history, population structure and human genetic diversity of TK-speaking.…”
Section: Demographic History and Population Structure Within Tk-speak...mentioning
confidence: 99%
See 1 more Smart Citation